Pelatihan Pengolahan Telur Asin menjadi Kerupuk dan Telur Asin Panggang untuk Meningkatkan Produktivitas dan Pengetahuan Kelompok PKK Desa Rowosari - Muh Khoyiman; Adib Al Hafizh; Riska Tri Susanti; Faiz Khoerul Anam; Miftakhur Rizki Hidayat Febrianto; Tjahja Muhandri (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Rowosari Village is one of the villages in Bonorowo District, Kebumen Regency which is dominated as an agricultural area. With the availability of abundant agricultural produce as animal feed, many farmers raise ducks to produce eggs. Duck eggs are a popular product in the community. One of the duck egg products is salted egg and salted egg crackers. The need for innovation in duck egg products to make it durable, one of which is made of salted egg crackers. This community service carried out in Rowosari Village aims to provide training on the process of making salted egg crackers, improving the family-based community economy. The training was conducted at the Rowosari Village Hall, RT 04 / RW 01, and was held from November 2020 - January 2021. Family Welfare Empowerment Cadres (PKK) who participated in this salted egg processing activity were 25 people and all of them were married. Extension activities were carried out by the LAWET IGTF (IPB Goes To Field Domicile) team, as a means of increasing the added value of duck egg products into innovative products and having higher selling value. The results of the questionnaire that have been carried out can be seen from the 20 extension participants, the points obtained before the extension were 148 points, while after counseling it increased to 190 points. This shows an increase in knowledge and insight from PKK women in Rowosari Village about salted egg crackers and roasted salted eggs. The taste of these egg crackers will be unique with the addition of the main ingredient of salted duck eggs. The composition used in the training for making salted egg crackers is salted egg, starch, wheat flour, salt, garlic, baking soda, coloring, and flavorings. Keywords: innovation, egg crackers, community service, economic improvement